Perancangan Model Bisnis E-Commerce untuk Meningkatkan Pemasaran Souvenir di Mandailing Natal - Mu'tada, Muhammad; Annas, Firdaus; Riski, Roni (Yayasan Lembaga Studi Makwa, 2024)
E-Commerce based Marketing System activities are the practice of using promotions to increase traffic to online stores E-Commerce based Marketing System activities are the practice of using promotions to increase traffic to online stores. This research aims to design an e-commerce business model to improve marketing of MSME souvenir products in Mandailing Natal Regency. Most business actors still use traditional methods, so product marketing and promotion is less than optimal. By utilizing the Opencart platform, this research develops a system that can expand market reach and transaction efficiency. This research uses the Research and Development (R&D) method With models ADDIE (Analysis, Design, Development, Implementation, Evaluation) model was chosen because it is suitable for developing e-commerce based promotional media. This research is expected to be a strategic solution to increase economic growth and marketing of typical Mandailing Natal products.